Dentistry applied to sports: Impacts on athletes' performance (Research, Society and Development, 2025)
The main objective of this study is to analyze the relationship between oral conditions and athletes' performance, emphasizing the importance of Sports Dentistry in preventing pathologies and orofacial injuries. Sports Dentistry is a specialty focused on the prevention and treatment of oral conditions that can directly interfere with athletes' physical performance. Diseases such as caries, periodontitis, temporomandibular disorders (TMD), endodontic infections, and bruxism are frequent among athletes and can compromise key factors such as muscle strength, endurance, concentration, sleep quality, and post-training recovery. The presence of often asymptomatic oral infections can trigger systemic inflammatory processes that affect metabolism, cause chronic pain, and reduce the body's efficiency during training and competitions. In addition, orofacial trauma in contact sports is common and can be prevented with the use of customized mouthguards, made by specialized dentists. The sports dentist also plays an important role in guiding oral hygiene habits, controlling stress factors that contribute to bruxism, and interacting with other health professionals, forming multidisciplinary teams focused on performance and the athlete’s overall health. Thus, Sports Dentistry proves to be essential not only for preventing and treating injuries but also as a strategic ally in optimizing performance and ensuring athletic longevity.